A mixed linear modelling characterisation of gender and speed related changes in spatiotemporal and kinematic characteristics of gait across a wide speed range in healthy adults. (October 2018) - Stansfield, Ben; Hawkins, Katrina; Adams, Sarah; Bhatt, Haseel
Highlights: Mixed linear modelling is used to explore changes in gait with gender and speed. Fully normalised analysis is performed across 775 trials of walking data. Normalised speed range of 0.10–0.55 – slowest to fastest possible walking speeds. Gender dependent speed related changes are identified in kinematic outcomes. Non-linear relationships of speed with spatiotemporal and kinematic characteristics. Abstract: In exploring the relationship between the kinematics of gait and speed of progression individual variation in patterns and gender differences have not always been adequately taken into account. In the current study mixed linear modelling was used to isolate changes with speed from those associated with individual variation and gender. Three-dimensional motion analysis of 20 participants (10M/10F, 25.7 ± 5.1 years) walking at a wide range of speeds (normalised speeds 0.10–0.55 ∼0.41–2.26 m/s) was recorded (775 walks). Spatiotemporal (speed, cadence, step length, percentage of single and double support) and kinematic characteristics (pelvis through ankle) were determined. Significant between participant differences were highlighted in both intercept and slope of relationships. In addition females exhibiting different peak pelvic tilt and obliquity, hip flexion and internal rotation and ankle dorsiflexion compared to males. Spatiotemporal parameters exhibited non-linear relationships with normalised speed ( R 2   > 0.5). Kinematic features exhibited significant relationships with normalised speed, varying from linear to cubic, from very weak to strong in fit (0.010 >  R 2   > 0.672). Mixed linear modelling highlighted gender dependent, speed related changes in addition to inter-individual variation. Gender and speed are both important determinants of gait patterns, however, individual variations remain.